Bombus brasiliensis Lepeletier (Hymenoptera, Apidae) infected with Nosema ceranae (Microsporidia) - Plischuk, Santiago (2016)
Heavy infections caused by a microsporidium were detected in midgut epithelium cells of two adult workers of the bumble bee Bombus brasiliensis Lepeletier collected near Puerto Iguazú, Misiones province, Argentina. Microsporidium rRNA (16S small subunit) was amplified by 218MITOC primers and produced amplicons indicating presence of Nosema ceranae Fries et al., a virulent pathogen of more than 20 bee species, possibly involved in Apis mellifera L. Colony Collapse Disorder. Campaigns in search of B. brasiliensis between 2008 and 2015 have revealed a possible narrower range in the southeastern area of its known distribution. Effects of N. ceranae infections could be modulating their populations and should not be overlooked. In addition, the wide host range of this microsporidium makes it a potential threat to several endemic bees such as stingless (Meliponini) and orchid bees (Euglossini).